Influence of "protective" symbionts throughout the different steps of an aphid–parasitoid interaction. Issue 4 (4th September 2020) - Sochard, Corentin; Bellec, Laura; Simon, Jean-Christophe; Outreman, Yannick
Abstract: Microbial associates are widespread in insects, some conferring a protection to their hosts against natural enemies like parasitoids. These protective symbionts may affect the infection success of the parasitoid by modifying behavioral defenses of their hosts, the development success of the parasitoid by conferring a resistance against it or by altering life-history traits of the emerging parasitoids. Here, we assessed the effects of different protective bacterial symbionts on the entire sequence of the host-parasitoid interaction (i.e., from parasitoid attack to offspring emergence) between the pea aphid, Acyrthosiphon pisum, and its main parasitoid, Aphidius ervi and their impacts on the life-history traits of the emerging parasitoids. To test whether symbiont-mediated phenotypes were general or specific to particular aphid–symbiont associations, we considered several aphid lineages, each harboring a different strain of either Hamiltonella defensa or Regiella insecticola, two protective symbionts commonly found in aphids. We found that symbiont species and strains had a weak effect on the ability of aphids to defend themselves against the parasitic wasps during the attack and a strong effect on aphid resistance against parasitoid development. While parasitism resistance was mainly determined by symbionts, their effects on host defensive behaviors varied largely from one aphid–symbiont association to another. Also, the symbiotic status of the aphid individuals had no impact on the attack rate of the parasitic wasps, the parasitoid emergence rate from parasitized aphids nor the life-history traits of the emerging parasitoids. Overall, no correlations between symbiont effects on the different stages of the host–parasitoid interaction was observed, suggesting no trade-offs or positive associations between symbiont-mediated phenotypes. Our study highlights the need to consider various sequences of the host-parasitoid interaction to better assess the outcomes of protective symbioses and understand the ecological and evolutionary dynamics of insect–symbiont associations.